Pengukuran Penerimaan Aplikasi Dreamspark Pada Stikom Surabaya Menggunakan Metode Technology Acceptance Model 3 - Prasetyo, Budiyanto; Sudarmaningtyas, Pantjawati; Mujayana, Marya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Dreamspark is a result of cooperation with Microsoft and Stikom Surabaya since 2001. Dreamspark provides legal softwares owned buy Microsoft which can be freely accese by students. In 2013-2016 legal download software in Dreamspark of 2,07%.One method that can measure behavior user of the technology is the method information technology acceptance model 3 ( tam 3 ). Tam3 is the result of development based on tam1. TAM 3 discusses the reciprocal relationship of invalid constructs (nomological network) determinant of why individuals adopt and use Information Technology (IT). In this study a test method using two measurements and structural methods, After going through two testing and expressed meet the standards can be conducted analysis using shem with the help of the application of SPSS.According to the analysis students received use application Dreamspark based on the mean on descriptive analysis of 2,2852, that it could be students can receive application of dreamspark is in supporting lecture. Variable behavioral intention have had a positive impact to use behavioral having the value estimation largest 0,740 and value of the probability of * * *. Said student get legal software for free lecture to help so as to make pengakses dreamspark could increase up at any time.